Mucormycosis and COVID-19: a skeleton in the closet and double burden for India - Saeed, Ahmad; Uzair, Muhammad; Eiman, Saadia; Younas, Hadia; Saeed, Komal (International Journal Of Community Medicine And Public Health, 2021)
Coronavirus chaos has enveloped India with highest daily death toll on 11th May with 4202 deaths and quite high positivity rates, over 21% countrywide. India is the second worst nation to suffer from pandemic having 20.80% share in global numbers. The Covid-19 recovered patients or those battling the virus with associated comorbidities and immunocompromised conditions are more vulnerable to develop the opportunistic black-fungal infections. A potentially fatal black-fungal infection is cropping up among Covid patients. Mucormycosis has claimed 70 lives with nearly 2000 diagnosed cases. Those with diabetes and heavy use of steroids to survive Covid-19 complications are worst affected.